1994
DOI: 10.1111/j.1365-2559.1994.tb01289.x
|View full text |Cite
|
Sign up to set email alerts
|

High frequency of Epstein–Barr virus in Chinese peripheral T‐cell lymphoma

Abstract: Forty-two cases of Chinese T-cell lymphoma were studied for expression of Epstein-Barr virus (EBV) encoded RNA (EBER-1) and EBV latent membrane protein-1 (LMP-1) using in situ hybridization and immunohistochemistry, respectively. EBV was detected in tumour cells in 24/39 peripheral T-cell lymphomas (62%), comprising 18/27 pleomorphic, medium and large cell lymphomas (67%), 4/6 angioimmunoblastic lymphadenopathy-like lymphomas (67%), 2/2 Lennert's lymphomas, 0/2 anaplastic large cell lymphomas, and 0/2 T-zone l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
31
1
4

Year Published

1996
1996
2006
2006

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(40 citation statements)
references
References 38 publications
4
31
1
4
Order By: Relevance
“…The EBER-ISH technique was found to be positive in 41% of patients, again paralleling the results of previous studies. 14,[17][18][19][20] The high sensitivity of the EBER-ISH technique compared with immunostaining, even in archival material, is well known 14,17,18,20 and illustrated here by the fact that LMP-1 was positive in only half of the EBER-ISHpositive cases.Although the type of treatment varied between protocol arms, all but one patient (109/110) were treated with an anthracyclinbased regimen. All patients 60 years or younger received an intensive regimen with curative intent.…”
mentioning
confidence: 67%
See 2 more Smart Citations
“…The EBER-ISH technique was found to be positive in 41% of patients, again paralleling the results of previous studies. 14,[17][18][19][20] The high sensitivity of the EBER-ISH technique compared with immunostaining, even in archival material, is well known 14,17,18,20 and illustrated here by the fact that LMP-1 was positive in only half of the EBER-ISHpositive cases.Although the type of treatment varied between protocol arms, all but one patient (109/110) were treated with an anthracyclinbased regimen. All patients 60 years or younger received an intensive regimen with curative intent.…”
mentioning
confidence: 67%
“…10,11 Epstein-Barr virus (EBV), the etiologic agent of infectious mononucleosis, has been linked to a wide range of tumors, mainly of B-cell origin. 12 Association of PTCLs with EBV has been first described in the late 1980s, 13 and has since been found to be present in an important fraction of cases in series from Asia [14][15][16][17][18][19] and from Western countries. [20][21][22][23] While some entities (angioimmunoblastic T-cell lymphoma 24 and extranodal NK/Tcell lymphoma, nasal type 25 ) are almost systematically associated with EBV, the frequency and signification of such an association among others is less well defined.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12) In DLBCL, Hummel et al 5) reported that EBER signals were expressed in tumor cells in 10 of 83 European cases (12%) by RNA-ISH. We found a similar frequency in Japanese cases (13 4,13) and one case in Hong Kong, 14) but most cases with EBV + DLBCL were negative for EBNA2.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies showed that PR was also an EBV-associated tumor, not only in the Oriental population (Harabuchi et al, 1990;Chan et al, 1994;Zhou et al, 1994;Peh et al, 1995;Tomita et al, 1995) but also in Western countries (Weiss et al, 1992;Kanavaros et al, 1993;Borisch et al, 1993). However, data to correlate EBV positivity and immunophenotype of PR are limited.…”
mentioning
confidence: 99%